Language acquisition in a post-pandemic context: the impact of measures against COVID-19 on early language development - Feijoo, Sara; Amadó, Anna; Sidera, Francesc; Aguilar-Mediavilla, Eva; Serrat, Elisabet (Frontiers in Psychology, 2023)
Language acquisition is influenced by the quality and quantity of input that language learners receive. In particular, early language development has been said to rely on the acoustic speech stream, as well as on language-related visual information, such as the cues provided by the mouth of interlocutors. Furthermore, children's expressive language skills are also influenced by the variability of interlocutors that provided the input. The Covid-19 pandemic has offered an unprecedented opportunity to explore the way these input factors affect language development. On the one hand, the pervasive use of masks diminishes the quality of speech, while it also reduces visual cues to language. On the other hand, lockdowns and restrictions regarding social gatherings have considerably limited the amount of interlocutor variability in children's input.The present study aims at analyzing the effects of the pandemic measures against Covid-19 on early language development. To this end, 41 children born in 2019 and 2020 were compared with 41 children born before 2012 using the Catalan adaptation of the MacArthur-Bates Communicative Development Inventories (MB-CDIs). Results do not show significant differences in vocabulary between pre-and post-covid children, although there is a tendency for children with lower vocabulary levels to be in the post-covid group. Furthermore, a relationship was found between interlocutor variability and participants' vocabulary, indicating that those participants with fewer opportunities for socio-communicative diversity showed lower expressive vocabulary scores. These results reinforce other recent findings regarding input factors and their impact on early language learning.